Chatbots, ChatGPT, and Scholarly Manuscripts: WAME Recommendations on ChatGPT and Chatbots in Relation to Scholarly Publications - Zielinski, Chris; Winker, Margaret; Aggarwal, Rakesh; Ferris, Lorraine; Heinemann, Markus; Lapeña, Jr, Jose Florencio; Pai, Sanjay; Ing, Edsel; Citrome, Leslie (Open Access Macedonian Journal of Medical Sciences, 2023)
Journals have begun to publish papers in which chatbots such as ChatGPT are shown as co-authors. The following WAME recommendations are intended to inform editors and help them develop policies regarding chatbots for their journals, to help authors understand how use of chatbots might be attributed in their work, and address the need for all journal editors to have access manuscript screening tools. In this rapidly evolving field, we expect these recommendations to evolve as well.